Exploring student and teacher perceptions of ChatGPT use in higher education: A Q-Methodology study - Alma S. Espartinez (Computers and Education: Artificial Intelligence)
This study examined and categorized the views of students and teachers in Philippine Higher Education Institutions (HEIs) and correlated those with similar patterns of views regarding ChatGPT usage. While previous studies explored ChatGPT's risks and benefits, a significant gap remains in understanding how college students and educators perceive this technology for its culturally relevant and equitable integration into teaching and learning. Using Q-Methodology, 27 participants (15 students and 12 professors) were surveyed, interviewed, and invited to rank-order 36 statements about using ChatGPT. Three factors emerged from using factor analysis: Ethical Tech Guardians, Balanced Pedagogy Integrators, and Convenience-Embracing AI Enthusiasts. Findings revealed diverse perceptions among college students and teachers regarding ChatGPT integration, identifying distinct factors reflecting ethical, innovative, and useful viewpoints. Recommendations are put forth to optimize ChatGPT and similar AI technologies in educational settings, including clear guidelines for assessment, cross-cultural studies, policy advocacy for ethical regulations, and further research on ethical considerations and cultural sensitivity.